Kontribusi Keterampilan Manajerial Kepala Madrasah dan Budaya Kerja terhadap Profesionalisme Guru Madrasah Aliyah - Noor Miyono; Dias Andris Susanto; Laela Wihdatul Arifah (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Teacher professionalism determines the quality of madrasas. Professional teachers are seen in the implementation of tasks characterized by good expertise in the material and methods in increasing student competence. Professional teachers will ensure the teaching and learning process and quality learning outcomes at madrasah. Teacher professionalism is influenced by many factors, including managerial leadership and work culture. This study aims to describe the influence of principal managerial skills and work culture in the school environment on the professionalism of private Madrasah Aliyah teachers in Semarang Regency. Research with a quantitative approach was conducted in the Semarang Regency area. The study population was teachers in 7 (seven) Private Madrasah Aliyah totaling 134 teachers and a sample of 100 respondents who were determined using a proportional random sampling technique. Data collection using a questionnaire. Correlation and regression tests used SPSS version 21 for Windows. The results of the study (1) there is an effect of managerial skills of madrasah principals on teacher professionalism by 20.8%, (2) there is an effect of work culture on teacher professionalism by 29.5% (3) there is an effect of managerial skills of madrasah principals and work culture on teacher professionalism Private Madrasah Aliyah Semarang Regency at 36.1%.